Blood product usage and factors associated with transfusions in cats with hemoperitoneum: 33 cases (2018–2022) - Bunnell, Nicole; Blong, April; Kundu, Debosmita; Mochel, Jonathan Paul; Walton, Rebecca (Frontiers in Veterinary Science, 2023)
Objective To evaluate blood product usage in cats with hemoperitoneum. To secondarily evaluate factors associated with transfusion administration and the outcome of cats with hemoperitoneum. Design Retrospective study between the years 2018–2022. Setting University veterinary teaching hospital and private practice hospital. Animals 33 cats admitted to the hospital diagnosed with hemoperitoneum from January 2018 to September 2022. Measurements and main results Medical records were retrospectively reviewed; signalment, point-of-care diagnostics, effusion characteristics, and transfusion administration information was recorded. The most common etiology associated with hemoperitoneum was neoplasia (51.5%). Fifty-one percent (51.5%) of cats received a blood transfusion during hospitalization with the majority of cats receiving multiple transfusion types (69%). The etiology of hemoperitoneum was not associated with receiving a transfusion (p = 0.28) Point-of-care diagnostics including packed cell volume (PCV), total solids (TS) and platelet count were not significantly associated with receiving a transfusion (p = 0.317, p = 0.11 and p = 0.82, respectively). The PCV and TS of the effusion was also not significantly associated with transfusions (p = 0.91 and p = 0.63, respectively). Sixteen cats (48%) survived to discharge. Transfusions were significantly associated with outcome and cats that received a transfusion were more likely to survive to discharge (p = 0.008). Conclusion In conclusion, hemoperitoneum from a variety of etiologies in cats is associated with a high proportion of transfusions. None of the evaluated point-of-care diagnostics were associated with transfusion administration in this study. Cats that received a transfusion were more likely to survive to discharge.